Patients with acute myocardial infarction treated at the department of cardiology of the provincial hospital of Las Tunas - Maikel Santos-Medina; Yurina Cruz-Fernández; Yorden Argüelles-Pons; Mailén Ailyn Marrero-Martínez; Efraín Manuel Borrero-Escobar (Revista Electrónica Dr. Zoilo E. Marinello Vidaurreta, 2022)
Background: the epidemiological characteristics of acute myocardial infarction have changed in the last decades.